The Image Theory as Explanation for the Attribution of Values in Criteria for Decision - Löbler, Mauri Leodir; Hoppen, Norberto; Estivalete, Vania de Fátima Barros (Review of Business Management, 2008)
This work has as goal to verify how the individuals deal with the information in a decision process when they have interests in reaching previously established results. A multicriterial decision task was used, solved with the aid of a TSS. The research method was experimental, using experimental groups divided by the level of knowledge on the decision object (popular cars). Two independent variables were also inserted in the experiment, the quality of the information and the complexity of the task. Three variables, one of personal feature (knowledge level) and two of task (complexity of the task and information’s quality) were inserted with intention to test variations in the use of decision makers’ information. It was concluded that the individuals commit greater intentionally number of trespasses in the attribution of weights, that is, transgress axioms of the multicriterial method to choose one previous defined alternative. There is, also, no relation between the linearity of the process and the trespasses, discarding the linearity as an explanation for the trespasses. The result of this study supplies indications to prove that the decision makers have strong conceptual values in its structure of knowledge at the beginning the decision process, and that, these values guide the subsequent process all. Key-words: Choice process. Image theory. Experts. Novices.